ڈاکٹر سید امجد حسین کے خاکوں میں ناسٹلجیائی عناصر - نیلم تاج; ڈاکٹر نذر عابد; ڈاکٹر محمد الطاف (Khayaban - خیابان, 2024)
Abstract: Nostalgia is a beautiful feeling of our past with a little bit of sadness. Listening to an old song, seeing an old picture or meeting an old friend creates a strange feelings in our heart. It creats a sadness with a strong wish that old time would come back again but we know that time cannot come back. That is why we get sad. This condition is called nostalgia. A piece of art cannot become a great piece of art unless it has the ability to shake the senses. Dr. Syed Amjad Hussain is such an artist who always shares his memories which create the elements of nostalgia in his creative works. In this article, the authors have analysed such nostalgic attitudes found in the various sketches written by Dr. Syed Amjad Hussain.